ANALISIS FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Gimin '; Sri Kartikowati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
The problems in this research was the factors that influence students’ learning motivation at economics department in faculty of teachers training and education of Riau university (i.e: motivation to learn in the classroom (Y1), motivation to carry out structured tasks (Y2), and motivation to learn independently (Y3)), particularly from external students (ie: the quality of lecturers (X1), the lecture method (X2), the conditions and atmosphere of the lecture hall (X3), the library facilities (X4), and the conditions and atmosphere of the park study (X5)). The participants of this research were the students of economics department at faculty of teachers training and education in Riau University in the academic year 2012/2013, the number of students is 294. This research was conducted in 50% samples (147 students), it was taken by the proportional technique of purposive sampling. The data were taken by using a questionnaire with four alternative answers. Furthermore, the data were analyzed by using descriptive analysis, regression, and partial correlation with the level of significance of 5%. The result of descriptive analysis found that the students generally have high motivation (to learn in the classroom, to do structured task, and to learn independently) respectively 86.4%, 87.1% and 88.4%. They also said that the quality of lecturers, the classroom conditions and atmosphere, as well as the library facilities are good, respectively 66.7, 59.2% and 45.6%. While the lecture method, as well as the conditions and atmosphere of the park study is enough to learn, respectively 59.2% and 51.7%. From the multiple regression analysis found that all of five independent variables (X1, X2, X3, X4, X5) have a significant effect on Y1, Y2, and Y3 with donations amounting to 22.8%, 24.2%, and 22.0%. While partially X1 and X2 have a significant relationship with Y1, Y2, and Y3. Unlike X5 which has a significant relationship with Y2 and Y3, but not significant with Y1. Whereas X2 has no significant relationship with the Y1, Y2, and Y3. Keywords: motivation, quality, methods, classrooms, libraries, parks